Diagnosis and management of arrhythmias in pregnancy. Issue 7 (14th December 2021) - Senarath, Sachintha; Nanayakkara, Pavitra; Beale, Anna L; Watts, Monique; Kaye, David M; Nanayakkara, Shane
Abstract: Arrhythmias are the most common cardiac complications occurring in pregnancy. Although the majority of palpitations in pregnancy may be explained by atrial or ventricular premature complexes, the full spectrum of arrhythmias can occur. In this article, we establish a systematic approach to the evaluation and management of arrhythmias in pregnancy. Haemodynamically unstable arrhythmias warrant urgent cardioversion. For mild cases of benign arrhythmia, treatment is usually not needed. Symptomatic but haemodynamically stable arrhythmic patients should first undergo a thorough evaluation to establish the type of arrhythmia and the presence or absence of structural heart disease. This will ultimately determine the necessity for treatment given the potential risks of anti-arrhythmic pharmacotherapy in pregnancy. We will discuss the main catalogue of anti-arrhythmic medications, which have some established evidence of safety in pregnancy. Based on our appraisal, we provide a treatment algorithm for the tachyarrhythmic pregnant patient. Graphical Abstract: